2017
DOI: 10.1038/srep40325
|View full text |Cite|
|
Sign up to set email alerts
|

KANK1 inhibits cell growth by inducing apoptosis through regulating CXXC5 in human malignant peripheral nerve sheath tumors

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are a type of rare sarcomas with a poor prognosis due to its highly invasive nature and limited treatment options. Currently there is no targeted-cancer therapy for this type of malignancy. Thus, it is important to identify more cancer driver genes that may serve as targets of cancer therapy. Through comparative oncogenomics, we have found that KANK1 was a candidate tumor suppressor gene (TSG) for human MPNSTs. Although KANK1 is known as a cytoskeleton regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…We found that CXXC5 is also downregulated in the majority of HCC tissue samples, leading to breakdown of CXXC5‐mediated positive feedback regulation of TGF‐β signaling and attenuation of its anti‐proliferative effects . In addition, CXXC5 is involved in KANK1‐induced cell growth inhibition and apoptosis in MPNSTs . However, it has also been shown that CXXC5 is overexpressed in ER+ breast cancer and associated with poor prognosis in patients .…”
Section: Pathophysiological Functions Of Cxxc5mentioning
confidence: 86%
See 3 more Smart Citations
“…We found that CXXC5 is also downregulated in the majority of HCC tissue samples, leading to breakdown of CXXC5‐mediated positive feedback regulation of TGF‐β signaling and attenuation of its anti‐proliferative effects . In addition, CXXC5 is involved in KANK1‐induced cell growth inhibition and apoptosis in MPNSTs . However, it has also been shown that CXXC5 is overexpressed in ER+ breast cancer and associated with poor prognosis in patients .…”
Section: Pathophysiological Functions Of Cxxc5mentioning
confidence: 86%
“…KANK1 is a potential tumour suppressor gene and is downregulated in more than half of human malignant peripheral nerve sheath tumours (MPNSTs) . Overexpression of KANK1 could induce CXXC5 expression to promote cell apoptosis in MPNSTs . The retinoic acid receptor (RARα) acts as a transcription factor when bound to all‐trans retinoic acid, facilitating terminal maturation of leukaemic blasts .…”
Section: Cxxc5 Functions At the Crossroads Of Multiple Signaling Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 More importantly, CXXC5 acted as a potential tumor suppressor, and it is the target gene of miR-32. 34,35 More importantly, CXXC5 acted as a potential tumor suppressor, and it is the target gene of miR-32.…”
Section: Discussionmentioning
confidence: 99%